2023
DOI: 10.3390/ijms25010296
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Mediated Hyperthermia and Cytotoxicity Mechanisms in Cancer

Vanessa-Meletia Bala,
Dimitra Ioanna Lampropoulou,
Stamatiki Grammatikaki
et al.

Abstract: Hyperthermia has the potential to damage cancerous tissue by increasing the body temperature. However, targeting cancer cells whilst protecting the surrounding tissues is often challenging, especially when implemented in clinical practice. In this direction, there are data showing that the combination of nanotechnology and hyperthermia offers more successful penetration of nanoparticles in the tumor environment, thus allowing targeted hyperthermia in the region of interest. At the same time, unlike radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Hyperthermia is described as a temporary abnormal increase in the temperature of a specific body part [1]. In the context of hyperthermia (HT), it is necessary to raise the temperature of the specific tissue to a range between 46 and 50 degrees Celsius, with the aim of causing cell death by either apoptosis or necrosis [2,3]. The thermal effect generated at high temperatures offers a viable route for targeting and incapacitating diseased cells, increasing their susceptibility to additional therapeutic modalities such as radiation therapy or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia is described as a temporary abnormal increase in the temperature of a specific body part [1]. In the context of hyperthermia (HT), it is necessary to raise the temperature of the specific tissue to a range between 46 and 50 degrees Celsius, with the aim of causing cell death by either apoptosis or necrosis [2,3]. The thermal effect generated at high temperatures offers a viable route for targeting and incapacitating diseased cells, increasing their susceptibility to additional therapeutic modalities such as radiation therapy or chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that various DOX nanoformulations caused a more pronounced antitumor effect in vitro and in vivo when combined with hyperthermia [ 37 , 38 , 39 ]. Comparisons between free DOX and LDOX given in combination with different hyperthermia methods (water bath and infrared heating) revealed a significantly greater inhibition of tumor growth and reduced toxicity profiles in experimental sarcoma models [ 27 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%